Integrating Morpho-Phenological and Agronomical Traits to Explore Genetic Diversity of Wheat (Triticum aestivum L.) Landraces in Lalitpur, Nepal - Bhattarai, Mukunda; Sha, Anjali; Udash, Mandira; Bohara, Shailendra (Agronomy Journal of Nepal, 2025)
Wheat (Triticum aestivum L.) is the king of cereal crops, with the largest genomic size ( 17 Gb), the oldest domesticated crop, with high and increasing demand, making its continuous crop improvement essential for climate resilience and food security. To characterize and evaluate 70 Nepalese wheat landraces, this research was carried out in the National Agriculture Genetic Resources Centre (NAGRC), Khumaltar, Lalitpur, from November 12, 2024, to May 22, 2025. Seventy wheat landraces collected from different districts of Nepal were characterized and evaluated using an augmented block design. Twenty quantitative and thirteen qualitative traits were assessed to determine the extent of variability and identify elite genotypes for breeding programs. Statistical tools like Principal Component Analysis (PCA), descriptive statistics, Cluster analysis, Karl Pearson correlation coefficient were used for the analysis. Shannon-Weaver diversity indices (H’) showed a moderate to low level of diversity for qualitative traits, and showed a high to moderate level of diversity for quantitative traits. The first four principal components (PC) explained 67.42% of the total phenotypic variation, while the first two PCs constituted 49.32% of the variation. Cluster analysis grouped the 70 wheat accessions into four genetically distinct clusters. Cluster-2 was the largest cluster with 35 (50%) accessions, and cluster-1 constituted 25 (35%) accessions. Pearson correlation analysis showed a highly significant positive correlation between days to heading and days to maturity, plant height and spike exertion, awn length and hundred grain weight, and seed length and hundred grain weight. Promising landraces were identified for high-yielding, desirable short-stature (lodging resistant), desirable early maturing traits, and quality seed-related traits for studying their suitable area of cultivation as elite candidates for evaluation across multiple environments and selection for potential use in the development of improved wheat varieties.